Influence of habitat structure on Pristimantis species (Anura: Craugastoridae) in a bamboo-dominated forest fragment in southwestern Amazonia - López-Rojas, Jhon Jairo; Souza, Moisés Barbosa; Morato, Elder Ferreira (Phyllomedusa: Journal of Herpetology, 2015)
Structural and determinate factors for the composition of assemblages of species are diverse. Two theories attempt to explain the pattern of species composition in assemblies using different approaches—i.e., Niche Theory and Neutral Theory. Anurans have complex responses to habitat structure. Species of Pristimantis are good indicators for conservation because they are organisms with direct development. The effect of habitat structure on species of Pristimantis in a bamboo-dominated remnant forest located in southwestern Amazonia is analyzed herein. Active visual and auditory searches in 10 plots of the Biodiversity Research Program (PPBio) were conducted between November 2012 and May 2013. Four hundred and sixty individuals of five species were recorded: Pristimantis altamazonicus, P. diadematus, P. fenestratus, P. reichlei, and P. skydmainus. Neither spatial distance nor the structure of the habitat of the plots affected the composition of Pristimantis. The first axis of PCA explained 45.6% variation of the characterization habitat structure, correlated significantly with the number of Pristimantis, species increasing with trees between 10 ≤ dbh < 30 cm and decreased with density of bamboo. The increase in litter depth and canopy cover influenced in the occurrence of P. reichlei, the occurrence of P. skydmainus decreased with increased density of bamboo and trees dbh ≥ 30 cm and the occurrence of P. diadematus decreased relative to increased canopy cover. Pristimantis diadematus and P. skydmainus were the most restricted species in terms of habitat and were especially susceptible to bamboo density.